Research of actual characteristics for describing of the target audience for digital marketing - D. A. Khokhlov (Вестник университета)
The article examines the current characteristics of the target audience in the digital marketing. The problem of the discrepancy between the classical ways of describing audiences and the advertising inventory of digital promotion channels has been actualised. Analysis of advertising campaigns and web analytics systems has identifed six main groups of characteristics that can be used to describe the target audience for any advertising service in the digital marketing. The new features complement existing audience description methods and allow target groups to be described in terms that are understandable to different specialists, and are available on any advertising channel in the digital marketing. The result of the study will increase the effectiveness of promotion in the digital space due to more precise settings of advertising messages.